Analysis of temperature and aging effects on biomedical ultra-high molecular weight polyethylene's grades using a viscoelastic model - Rui Miranda Guedes (2011)
The applicability of a proposed viscoelastic model, previously developed to model dynamic behaviour of ultra-high molecular weight polyethylenes (UHMWPE), was assessed using three different UHMWPE medical grades. The dynamic data, collected from literature, was obtained via DMTA (Dynamic Mechanical Thermal Analysis) operated over a wide temperature and frequency range. The time-temperature superposition principle (TTSP) was applied to dynamic data via the proposed viscoelastic model. A reference temperature of 37 degrees C was selected. It was verified that both horizontal and vertical shifts are necessary to superimpose the dynamic modulus/frequency curves of all UHMWPE grades. Moreover, it was shown that the aging effect can be modelled using an aging-time superposition principle based on the proposed viscoelastic model. Again, both horizontal and vertical shifts were necessary to superimpose the aged and non-aged dynamic modulus/frequency curves at 37 degrees C.